Artificial General Intelligence - Goertzel, Ben; Pennachin, Cassio (Cognitive Technologies, 2007)
This is the first book on current research on artificial general intelligence (AGI), work explicitly focused on engineering general intelligence - autonomous, self-reflective, self-improving, commonsensical intelligence. Each author explains a specific aspect of AGI in detail in each chapter, while also investigating the common themes in the work of diverse groups, and posing the big, open questions in this vital area. The book will be of interest to researchers and students who require a coherent treatment of AGI and the relationships between AI and related fields such as physics, philosophy, neuroscience, linguistics, psychology, biology, sociology, anthropology and engineering.